Reconceptualizing Islamic Primary Education: A Comparative Multiple Case Study of a Qur’anic–Montessori Hybrid Pedagogical Framework in Indonesia and Malaysia - Ade Aspandi; Aip Syarifudin; Muhammad Azhar Muttaqin; Mamat Rahmatullah (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This study addresses the gap between Islamic value-based education and contemporary child-centered pedagogies, which are often examined separately in previous research. It aims to analyze how an integrative Qur’anic curriculum can be effectively implemented within a Montessori-based framework in Islamic primary schools across Indonesia and Malaysia. This research employs a qualitative multiple case study design, using comparative analysis of selected Islamic schools that adopt integrative and Montessori-inspired practices. The findings indicate that integrating Qur’anic values with Montessori pedagogy fosters a holistic learning environment that supports students’ cognitive, social, emotional, and spiritual development. The use of mixed-age classrooms and prepared learning environments encourages autonomy, collaboration, and meaningful engagement, while spiritual practices are embedded within daily learning activities as lived experiences. This study contributes by proposing an integrative Qur’anic–Montessori model as a hybrid pedagogical framework that bridges religious education and modern learner-centered approaches. The findings offer practical and theoretical implications for developing holistic and value-oriented Islamic education systems in both local and broader international contexts.